Вивчення явища спадковості при трансформації структури в сталях - Носонова, Любов В’ячеславівна; Ніконоров, Олексій Сергійович; Кондратюк, Станіслав Євгенович (Eastern-European Journal of Enterprise Technologies, 2009)
This article describes the contemporary scientific understanding of the phenomenon of heredity in metals and alloys, of heredity, the mechanism of this phenomenon at various stages of manufacture of parts and its influence on the physicomechanical and performance properties of finished parts.